Global warming as the main abiotic factor in the formation of phytosanitary conditions under current terms - Fedorenko, A.V.; Galagan, T.O. (Quarantine and plant protection, 2026)
Goal. To investigate the long-term dynamics of the temperature regime in Ukraine as a key abiotic environmental factor determining the state of pest populations. To study the patterns of its changes as a basis for compiling a further phytosanitary forecast. Methods. Theoretical analysis (structural-functional and systems approaches) — for the analysis and generalization of statistical data; field methods — conducting systematic phytosanitary monitoring. Results. During the period 2005—2024, climate change in Ukraine manifested itself through an increase in the average annual temperature compared with the long-term average data (average for 1986—2005) and, as a consequence, through an increase in the sum of effective temperatures (SET). In general, the annual SET in Ukraine increased by 266.62°C; in the Steppe zone — by 307.21°C; in the Forest-Steppe — by 274.31°C; and in Polissya — by 222.88°C. The trend lines of the graphs of the long-term dynamics of SET indicators during 2005—2024, both on average for Ukraine and for each natural-climatic zone, indicated a gradual increase in the temperature regime. However, the intensity gradually decreased, and the growth of SET almost stopped starting from 2013. A comparison of data from Kyiv meteorological stations for different periods (over more than the last hundred years) also confirms climatic changes towards warming: the average annual temperature in 2015—2024 exceeds the corresponding indicator at the end of the 19th century (1871—1880) by more than 3°C. Weather conditions in 2024 were especially hot, when in general across Ukraine the SET exceeded the corresponding long-term average value by 607.5°C. Conclusions. The analysis of the long-term dynamics of air temperature showed an increase in the average annual temperature and in the sum of effective temperatures. However, the intensity of SET growth has almost ceased since 2013.